An updated checklist of the mosquitoes (Diptera: Culicidae) present in Algeria, with assessments of doubtful records and problematic species - Merabti, B.; Boumaza, M.; Ouakid, M.l.; Carvajal, Thaddeus M.; Harbach, Ralph E. (Zootaxa, 2021)
An updated checklist of the mosquitoes (Diptera: Culicidae) of Algeria based on records published from 1903 to 2021 is presented. Fifty-three species belonging to seven genera are known with reasonable confidence to occur in the country, including Aedes (15 species), Anopheles (15), Coquillettidia (2), Culex (14), Culiseta (5), Orthopodomyia (1) and Uranotaenia (1). Two additional species, Culex simpsoni Theobald, 1905 and Uranotaenia balfouri Theobald, 1904, are provisionally regarded as present in Algeria. Published records are listed for each species, with indication of synonymous usage and variant spelling of names where applicable. The type locality of Aedes biskraensis Brunhes, 1999 is restricted to Seriana in Sidi Okba District in Biskra Province. Problematic species and doubtful occurrence records based on apparently misidentified specimens and confused taxonomy are discussed. Notes on taxonomy and medical importance are provided for the more important species.